Caenorhabditis elegans as a tool for environmental risk assessment: emerging and promising applications for a "nobelized worm". (28th May 2019) - Queirós, L.; Pereira, J. L.; Gonçalves, F. J. M.; Pacheco, M.; Aschner, M.; Pereira, P.
Abstract: Caenorhabditis elegans has been an invaluable model organism in research fields such as developmental biology and neurobiology. Neurotoxicity is one of the subfields greatly profiting from the C. elegans model within biomedical context, while the corresponding potential of the organism applied to environmental studies is relevant but has been largely underexplored. Within the biomedical scope, the implication of metals and organic chemicals with pesticide activity (hereinafter designated as pesticides) in the etiology of several neurodegenerative diseases has been extensively investigated using this nematode as a primary model organism. Additionally, as a well-known experimental model bearing high sensitivity to different contaminants and representing important functional levels in soil and aquatic ecosystems, C. elegans has high potential to be extensively integrated within Environmental Risk Assessment (ERA) routines. In spite of the recognition of some regulatory agencies, this actual step has yet to be made. The purpose of this review is to discuss the major advantages supporting the inclusion of C. elegans in lower tiers of ERA. Special emphasis was given to its sensitivity to metals and pesticides, which is similar to that of other model organisms commonly used in ERA (e.g. Daphnia magna and Eisenia sp.), and to the large array of endpoints that can be tested with the species, both concerning the aquatic and the soil compartments. The inclusion of C. elegans testing may hence represent a relevant advance in ERA, providing ecologically relevant insights toward improvement of the regulatory capacity for establishing appropriate environmental protection benchmarks.